Short-Term Diet Restriction but Not Alternate Day Fasting Prevents Cisplatin-Induced Nephrotoxicity in Mice - Gunebakan, Evrin; Yalcin, Esra; Cikler Dulger, Esra; Yigitbasi, Ahmet; Ates, Nilay; Caglayan, Aysun; Kilic, Ertugrul (Mdpi, 2020)
Cisplatin (CP) is one of the most preferred platinum-containing antineoplastic drugs. However, even in nontoxic plasma concentrations, it may cause kidney injury. To be able to increase its effective pharmacological dose, its side effects need to be regarded. Diet restriction (DR) has been demonstrated to improve cellular survival in a number of disorders. In this context, we investigated the role of DR in CP-induced nephrotoxicity (CPN). Besides alternate DR, animals were exposed to DR for 3 days prior or after CP treatment. Here, we observed that both 3 days of DR reverses the nephrotoxic effect of CP, which was associated with improved physiological outcomes, such as serum creatine, blood-urea nitrogen and urea. These treatments significantly increased phosphorylation of survival kinases PI3K/Akt and ERK-1/2 and decreased the level of stress kinase JNK were noted. In addition, the activation level of signal transduction mediator p38 MAPK phosphorylation was higher particularly in both three-day DR groups. Next, animals were fed with carbohydrate-, protein- or fat-enriched diets in the presence of CP. Results indicated that not only fasting but also dietary content itself may play a determinant role in the severity of CPN. Our data suggest that DR is a promising approach to reduce CPN by regulating metabolism and cell signaling pathways.
Keywords: cisplatin; fasting; renal protection; acute kidney injury; nephrotoxicity; MAPK pathway